Úlceras venosas: caracterização e tratamento em usuários atendidos nas salas de curativos da rede municipal de saúde de Goiânia-GO - SANT\'ANA, Sílvia Maria Soares Carvalho (2011)
The venous ulcer is a public health problem according to the number of people affected and because of its chronic character, being the main cause of ulcers of the lower limbs. The injuries alter domestic activities, work and leisure activities, doing it necessary to the acting of a multidisciplinary team, which includes the nurse as a professional who, every day, assesses the health of the person, carrying out the curative, runs educational actions and makes referrals. The care of this population is realized, in mostly, on basic health units, yet the polls are usually conducted in reporting units, which contributes to know only part of the affected population. We aimed to analyze the socioeconomic, demographic and clinical profile of people with venous ulcers treated in curative rooms of the municipal health network and to analyze the treatment performed on the units and at home. We conducted a clinical study, observational, descriptive, cross-sectional with quantitative approach, involving people with venous ulcers, users of the curative rooms of the municipal health network of Goiânia, Goiás. Data collection was conducted from October 2009 to July 2010. It occurred through interviews, physical examination, application of evaluation scale of healing, refers to diagnostic procedures for amending the venous circulation of lower limbs and photography of the lesion, using a standardized guide. The 58 (100%) subjects tested ranged in age from 28 to 79, 39 (67.2%) were male, 42 (72.4%) were up to five years of study, 39 (67.2%) were working, 28 (48.3%) were in economy class "D". It was observed that 21 (36.2%) had hypertension, 10 (17.2%) diabetes, 30 (51.7%) higher body mass index, 39 (67.2%) spent most of the day sitting or lying. The lower limbs had varicose veins, reticular veins or telangiectasia (87.9%), hyperpigmentation (84.8%), edema (83.3%), lipodermatosclerosis (53.0%), eczema (51.5%) and pain (60.6%). Approximately half of the lesions were recurrent, people had a predominantly affected limb with a single lesion, with more than one-year duration; areas of lesions were greater than 24cm2, predominantly in the slough bed and a large amount of exudates, indicating a state of healing impaired. The borders were circled, regular, adhered and elevated; the perilesional skin showed fine texture (75.5%), shiny, scaly, with hyperthermia and hyperemia. The treatment occurred with the accompanying professional of technician or nursing assistant, nurse and doctor (56.9%), four people (7.0%) only with the technician. The product used in treatment was, mainly, based on essential fatty acid, four (6.9%) people used Unna s boot and three (5.1%), drug therapy. The majority (67.2%) was also curative at home, and in 17 (29.3%) cases, cleaning carried out with water. The results of this study indicate a population with poor socioeconomic conditions, presenting chronic disease with lesions characteristically deteriorated; pointing to needs of treatment, those consider the people in their entirety, which involves actions planned and ongoing, systemic and local impact.